2010
DOI: 10.1021/jp100533w
|View full text |Cite
|
Sign up to set email alerts
|

Electric Field Control of Surface Oxygen Dynamics and its Effect on the Atomic Scale Structure and Morphology of a Growing Ultrathin Oxide Film

Abstract: Controlled manipulation of oxide microstructure and morphology is critical to achieve the desired chemical activity in a variety of applications involving nanoscale metal oxides. The kinetics of surface oxide growth is strongly correlated to the microstructure of the developing oxide film, i.e., structure, morphology, and chemical composition. Controlling oxide microstructure and surface oxide coverage in the case of discontinuous oxide growth on metal substrates exhibiting slow oxidation kinetics remains a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 64 publications
1
16
0
Order By: Relevance
“…Then, the ionized molecules diffuse into existing defects and dissociate leading to O 2À ions which then require further surface diffusion to find available oxygen vacancies. 92 Once the oxygen molecules complete the surface reactions, if the resulting ions are near a pore, they diffuse through it in the vertical direction and then along the a-b plane (Fig. 12).…”
Section: Discussionmentioning
confidence: 99%
“…Then, the ionized molecules diffuse into existing defects and dissociate leading to O 2À ions which then require further surface diffusion to find available oxygen vacancies. 92 Once the oxygen molecules complete the surface reactions, if the resulting ions are near a pore, they diffuse through it in the vertical direction and then along the a-b plane (Fig. 12).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that a significant impact on the oxidation kinetics can be achieved by either directly applying an external electric field [3][4][5][6][7][8][9][10] or electron bombardment of the oxide surface [11][12][13]. We demonstrate here that the actual value of the self-generated electrostatic potential (designated as the kinetic potential [14]) can deviate from the Mott potential and is tunable by varying the oxygen pressure during oxidation which provides control of the limiting thickness of the oxide film.…”
mentioning
confidence: 99%
“…Since the applied electric field may affect both crystallization and oxidation processes [15,16], it results in the limitation on the mutual diffusion of nickel, iron, and oxygen atoms and the occurrence of the numerous dynamic processes involved in the solid state reactions, including both metals atoms nucleation and surface oxygen diffusion could take place [17]. This phenomenon may take place because of oxygen ionization processes in the vapor condensation zone.…”
Section: Methodsmentioning
confidence: 99%
“…The formation and evolution of mixed oxide domains in the particles are also primarily dictated by the surface oxygen dynamics -uptake and surface mobility, which are strongly depended on the applied electric field. At zero electric field, the activation energy barriers for ionic migration are still high enough to ensure lower oxygen surface mobility [16]. Increasing the oxygen partial pressure increases the rate of oxide nucleation, which couples to the enhanced surface mobility of oxygen atoms in the presence of electric field [12].…”
Section: Methodsmentioning
confidence: 99%